2011
DOI: 10.1097/dbp.0b013e318210ff2c
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Illness Uncertainty to Parent and Youth Adjustment in Juvenile Rheumatic Diseases: Effect of Youth Age

Abstract: : Parental uncertainty due to illness seems to be more predictive of both parent and youth distress with increasing youth age. These findings indicate that the impact of parental illness uncertainty on adjustment outcomes is pronounced as children transition into developmental periods of increasing autonomy and independence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…This was 0.91 for the total scale , while component reliability measures ranged from 0.87 for ‘ambiguity’ to 0.72 ‘unpredictability’. Reliability was further confirmed through subsequent testing among parents of critically ill children (α = 0.92), spina bifida (α = 0.81), leukaemia (α = 0.90), cystic fibrosis (α = 0.89) , diabetes mellitus type 1 (α = 0.88) and juvenile rheumatic diseases (α = 0.88) .…”
Section: The Studymentioning
confidence: 97%
See 1 more Smart Citation
“…This was 0.91 for the total scale , while component reliability measures ranged from 0.87 for ‘ambiguity’ to 0.72 ‘unpredictability’. Reliability was further confirmed through subsequent testing among parents of critically ill children (α = 0.92), spina bifida (α = 0.81), leukaemia (α = 0.90), cystic fibrosis (α = 0.89) , diabetes mellitus type 1 (α = 0.88) and juvenile rheumatic diseases (α = 0.88) .…”
Section: The Studymentioning
confidence: 97%
“…cancer, Cardiac conditions, HIV) . It has been shown to be a useful outcome measure in the support of parents of children suffering chronic health problems such as diabetes mellitus , juvenile arthritis , cancer and similar complex conditions . It has been found useful in both acute and critical illnesses .…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the child's level of vision is important not only because uncertainty compounds parental distress,9 but also to form the basis for advice on vision and developmental promotion. A detailed history that invites open descriptions is particularly helpful in children with a low level of vision or in children with limited movement and vocalisation 10.…”
Section: Diagnosis and Assessmentmentioning
confidence: 99%
“…A majority of parents in the current study had children with JIA who were less than 12 years old. Fedele et al (23) found that the association between parental uncertainty and parental distress was greater in parents of older children and that parental uncertainty was related to increased child depressive symptoms in older, but not younger, children. It may be that other issues around uncertainty would have been identified if we had recruited more parents of older children.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies of uncertainty have been conducted with parents of children with juvenile rheumatic diseases (a majority of whom had JIA) and found that parent perceptions of illness uncertainty were related to parent and child distress (22,23). These studies reported illness uncertainty using a single dimension score, whereas research by Cleanthous et al in adult rheumatological disease (24) found that illness uncertainty is multidimensional, incorporating five domains, namely, uncertainty relating to symptoms and prognosis, medical management, self‐management, impact, and social functioning.…”
Section: Introductionmentioning
confidence: 99%